Accounting Information Systems (Book). - Burns, Thomas J.; Ginzberg, Michael J. (The Accounting Review, 1979)
Abstract Reviews the book "Accounting Information Systems," by Robert G. Murdick, Thomas C. Fuller, Joel E. Ross and Frank J. Winner-Mark.